Executive overconfidence and securities class actions - BANERJEE, Suman (Institutional Knowledge at Singapore Management University, 2018)
Overconfident CEOs/senior executives tend to have excessively positive views of their own skills and their company’s future performance. We hypothesize that overconfident managers are more likely to engage in reckless or intentional actions/disclosures that give rise to securities class actions (SCAs). Empirical evidence is supportive: Overconfident CEOs/senior executives increase SCA likelihood, though litigation risk is ameliorated through improved governance, such as following the Sarbanes–Oxley Act of 2002. Post-SCA, companies are less likely to hire an overconfident CEO. Following an SCA, overconfident CEOs appear to moderate behavior and to reduce their litigation risk.